Implementasi Green Marketing terhadap Sikap Konsumen Kosmetik Alami PT. Best One Natural - Ari Astiti; Yaktiworo Indriani; Wuryaningsih Dwi Sayekti (Politeknik Pembangunan Pertanian Malang, 2024)
Enviromental issue stimulate growth of green marketing. The aims of this research are to evaluate implementation of green marketing and attitude of natural cosmetics consumens at PT Best One Natural in case to support green cosmetics marketing. Data collection in July to September 2023 at Terusan Nunyai, Lampung Tengah. The research method used is case study which is analized by qualitative and quantitative descriptive. The samples are consumers of PT Best One Natural which are recruited by random sampling. Total respondens are 54 consumers. Data analyzed by descriptive analysis, namely Multiatribut Fishbein and Ideal model for analyse Consumer Behaviour. Analyze of this research showed that PT Best One Natural have implement green marketing in green product specially at quality aspect and minimalize product waste, then still optimalize at green price, green promotion also green place aspect. The research show that consumers like Best One Natural products with the highest score on the quality attribute and the lowest score on the price attribute. Consumers stated that the highest ideal model was for the longlasting fragrance attribute and the lowest ideal value was for the label attribute. Keywords : consumer attitude, green marketing, natural cosmetics